The training of wrist arthroscopy - Shi, Haifei; Lu, Pan; Yu, Dongdong; Wang, Jiwen; Wang, Zhenhua; Zhuang, Baotang; Shao, Chao; Liu, Chang; Liu, Bo (Frontiers in Medicine, 2022)
The wrist joint has the most complex anatomical structure of the human body. Patients with wrist-related diseases increasingly prefer minimally invasive procedures for wrist joint diagnosis and treatment. Wrist arthroscopy offers direct visualization of the structures of the joint anatomy and existing disease processes while causing minimal damage to surrounding soft tissue. However, it requires a high level of technical ability for wrist arthroscopy practitioners. Therefore, an improved focus on wrist arthroscopy training combining new educational media and traditional practice should aid in the development of novel wrist arthroscopy training mode. This article aims to describe the status of wrist training and evaluation systems and introduce a new progressive wrist training system.